The Microbiology Characteristics of Infected Branchial Cleft Anomalies. Issue 3 (July 2019) - Hirshoren, Nir; Fried, Neta; Weinberger, Jeffrey M.; Eliashar, Ron; Korem, Maya
Objectives: To investigate the microbiology profile of infected branchial cleft anomalies compared to deep neck infection and explore the influence of age on culture findings. Study Design: A retrospective case control study. Setting: A single tertiary medical center. Subjects and Methods: Patients treated for branchial cleft anomalies between 2006 and 2016 were included. Demographic data, disease and treatment parameters, and microbiology profile, including bacteria classification, antibiotics resistance patterns, and number of pathogens, were analyzed. Results: Of 278 cases treated for branchial cleft anomalies, we have analyzed 69 cases with infection and pathogen identification. The proportion of monobacterial infections was higher (70.6% vs 44.3%; P = .003; odds ratio [OR], 3.02) and the proportion of Streptococcus species infection was lower (48.9% vs 77.2%; P = .001; OR, 0.282) among the infected branchial cleft cases compared to deep neck infections. Anaerobic bacteria infection did not differ between groups (17.8% and 16.5%, respectively). There was a nonsignificant tendency toward more resistant bacterial strains among the infected branchial clefts (15.6% vs 6.3%; P = .118; OR, 2.726). There was no difference between the bacterial profile of patients younger or older than 16 years. Conclusions: The microbiology profile of infected branchial cleft anomalies is not age related and is different from that of deep neck infections. We demonstrate a relatively high frequency of monobacterial infections, relatively lower streptococcal infection rates, and a substantial contribution by resistant species and anaerobes. Empiric antibiotic treatment should cover Streptococcus species, including penicillin-resistant species, as well as clindamycin-resistant anaerobes.